2016
DOI: 10.1051/0004-6361/201628857
|View full text |Cite
|
Sign up to set email alerts
|

Pulsations powered by hydrogen shell burning in white dwarfs

Abstract: Context. In the absence of a third dredge-up episode during the asymptotic giant branch phase, white dwarf models evolved from low-metallicity progenitors have a thick hydrogen envelope, which makes hydrogen shell burning be the most important energy source. Aims. We investigate the pulsational stability of white dwarf models with thick envelopes to see whether nonradial g-mode pulsations are triggered by hydrogen burning, with the aim of placing constraints on hydrogen shell burning in cool white dwarfs and o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
(51 reference statements)
0
12
0
4
Order By: Relevance
“…In this work, we extend the work of [2] who showed that low-luminosity DA WDs exhibit pulsations excited by the ε mechanism, and now, we concentrate on the high-luminosity phase. Figure 3.…”
Section: Introductionmentioning
confidence: 76%
“…In this work, we extend the work of [2] who showed that low-luminosity DA WDs exhibit pulsations excited by the ε mechanism, and now, we concentrate on the high-luminosity phase. Figure 3.…”
Section: Introductionmentioning
confidence: 76%
“…Este mecanismo actua debido a la quema nuclear y es siempre desestabilizante. Los resultados de este trabajo 20 se encuentran publicados en la revista Astronomy & Astrophysics (Camisassa et al, 2016b), y serán descriptos en el Capítulo 5.…”
Section: Resumen De Los Resultados De La Tesisunclassified
“…Los resultados presentados en este Capítulo se ecuentran respaldados por una publicación en la revista A&A (Camisassa et al, 2016b).…”
Section: Pulsaciones Excitadas Por La Quema De Hidrógeno En Enanas Blunclassified
See 1 more Smart Citation
“…Los cálculos pulsacionales realizados en ésta tesis corresponden a modos de pulsación no radiales, en una aproximación adiabática. El LP-PUL ha sido empleado en diversos estudios pulsacionales tanto en estrellas enanas blancas (Camisassa et al, 2016;Córsico et al, 2016), como en estrellas δ Scuti y γ Doradus (Sánchez Arias et al, 2017) y GW Virginis . Este código numérico resuelve las ecuaciones diferenciales que gobiernan las pulsaciones no-radiales, lineales y adiabáticas en estrellas esfericamente simétricas (tales ecuaciones son revisadas en el apéndice A).…”
Section: Código De Pulsacionesunclassified